The association between duration of muscle exercise and psychological symptoms is higher in boys than in girls: A cross-sectional study based on Chinese college students during COVID-19 - Ouyang, Yu; Hong, Yu; Cheng, Jun; Cao, Hongmin (Frontiers in Pediatrics, 2022)
Objective The COVID-19 pandemic has had many negative effects on the physical and mental health of college students. Although many studies have analyzed the association between muscular fitness and psychological symptoms in children and adolescents, research during the COVID-19 pandemic is limited. Our study focused on analyzing the association between duration of muscle exercise and psychological symptoms among Chinese college students during the COVID-19 pandemic. Method A four-stage stratified whole-group sampling method was used to investigate basic demographic information, duration of muscle exercise and psychological symptoms in 5,559 college students aged 19–22 years in China. Chi-square test (categorical variables) and one-way ANOVA (continuous variables) were used to compare the psychological symptoms of college students with different durations of muscle exercise. Logistic regression analysis was used to analyze the association between duration of muscle exercise and psychological symptoms. Result The detection rate of psychological symptoms among Chinese college students was 9.0%; the detection rate was 10.7% for boys and 7.6% for girls. The proportions of duration of muscle exercise at <30 min/d, 30–60 min/d, and >60 min/d were 75.0%, 20.4%, and 4.6%, respectively. After adjusting for relevant confounding variables, taking Chinese college students with duration of muscle exercise >60 min/d as the reference group, duration of muscle exercise <30 min/d was positively correlated with the occurrence of psychological symptoms (OR: 4.19, 95%CI: 1.82, 9.61) (P < 0.001). In emotional symptoms (OR: 4.56, 95%CI: 1.99, 10.44), behavioral symptoms (OR: 3.44, 95%CI: 1.79, 6.60), social adaptation difficulties (OR: 3.04, 95%CI: 1.62, 5.68) dimensions, there is also a positive correlation (P < 0.01). Conclusions The negative association between duration of muscle exercise and psychological symptoms among Chinese college students also suggests that longer duration of muscle exercise among college students is associated with a lower prevalence of psychological symptoms. The association between duration of muscle exercise and psychological symptoms was higher in boys compared to girls.